Aspectos ecológicos e biotecnológicos das microalgas para conservação e preservação do Rio Toledo - Castro, Guilherme Miola de (2017)
This work aimed to address the ecological and biotechnological aspects of microalgae for the preservation and conservation of the Toledo River. The study was carried out in five points in the Toledo River, with monthly collections of 300 mL of samples, filtered in phytoplankton networks of 20 μm in diameter, from July / 2015 to June / 2016. The phytoplankton community and the concentration of chlorophyll a were identified at the genus level. The abiotic parameters pH, conductivity, turbidity, ammonia, nitrite, nitrate, orthophosphate, total phosphorus and, BOD as the Carlson Trophic State Indexes modified by Lamparelli and Nygaard were determined. In the evaluation of the growth of the microalgae collected from the Toledo River, four strains were used, two mixed (with two or more genera) and two isolates of Chlorella sp, divided into four treatments, all in the synthetic medium BM, during 18 days with monitoring of Kinetics of growth and pH every 2 days. The water quality of the Toledo river was directly affected by the urban activities in its surroundings, mainly in the points P4 and P5. 41 genera of algae were identified, divided into 5 classes, 10 orders and 20 families, with predominance of Chlorophyceae (44%). Spatially, point P4 was the most representative in number of genera with 28 taxa and, seasonally, the summer season presented 30 taxa, the largest of the four seasons of the year. In the IET of Lamparelli, the river was classified as oligotrophic and, in Nygaard from oligotrophic to mesotrophic. The growth of microalgae was influenced by the number of genera present in the strain and by the algal inoculum of the culture. The unialgal T4 strain had the highest maximum cell density - DCM of 4960 x 105 cells mL-1 and the lowest DCM was recorded by mixed T2 cultivation with 513 x 105 cells mL-1. The pH remained in alkaline condition in most of the experiment, favoring the availability of the HPO4- orthophosphate fraction. In the ecological aspects evaluated, the composition of the phytoplankton of the Toledo River was directly affected by the anthropic activities of its surroundings, mainly in the urban stretch and it was not possible to affirm the real trophic state of the Toledo River, by the two models using completely different methodologies, A third index should be tested to confirm the trophic degree of the river. In biotechnology, the growth of the non-mixed cultures was higher than the mixed ones and the alkaline pH is the most adequate cultivation condition for the growth of the analyzed microalgae.